2019
DOI: 10.1038/s41467-019-08833-7
|View full text |Cite
|
Sign up to set email alerts
|

Design strategy for serine hydroxymethyltransferase probes based on retro-aldol-type reaction

Abstract: Serine hydroxymethyltransferase (SHMT) is an enzyme that catalyzes the reaction that converts serine to glycine. It plays an important role in one-carbon metabolism. Recently, SHMT has been shown to be associated with various diseases. Therefore, SHMT has attracted attention as a biomarker and drug target. However, the development of molecular probes responsive to SHMT has not yet been realized. This is because SHMT catalyzes an essential yet simple reaction; thus, the substrates that can be accepted into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Increased SHMT activity is associated with increased demand for DNA synthesis in rapidly proliferating cells [47]. In recent years, SHMT has been shown to be associated with various diseases and has emerged as an important biomarker and drug target [48, 49]. Our previous studies confirmed that SHMT is the target gene of mosquito-specific miR-1174.…”
Section: Discussionmentioning
confidence: 71%
“…Increased SHMT activity is associated with increased demand for DNA synthesis in rapidly proliferating cells [47]. In recent years, SHMT has been shown to be associated with various diseases and has emerged as an important biomarker and drug target [48, 49]. Our previous studies confirmed that SHMT is the target gene of mosquito-specific miR-1174.…”
Section: Discussionmentioning
confidence: 71%
“…SHMT has been shown to be strongly upregulated in cancer cells , which have an increased demand for DNA synthesis , making the enzyme an attractive chemotherapy drug target. In spite of its increasing importance and numerous biochemical and drug development studies, there are still no SHMT inhibitors in clinical use, or in clinical trials .…”
mentioning
confidence: 99%
“…In our previous study, we performed high-throughput screening of inhibitors targeting hSHMT1 utilizing a fluorescent molecular probe for monitoring hSHMT activity ( Nonaka et al., 2019 ); we obtained two specific candidate inhibitors of hSHMT, one of which was glycodeoxycholic acid (Gly-DCA). In this study, we successfully obtained the crystal of hSHMT bound with Gly-DCA.…”
Section: Resultsmentioning
confidence: 99%
“… (B) ITC profiles of hSHMT1-Gly-DCA and hSHMT2-Gly-DCA interactions. Calorimetric data for hSHMT1 were obtained from our previous report ( Nonaka et al., 2019 ). (C) The binding of Gly-DCA with hSHMT1 or hSHMT2 assessed using differential scanning calorimetry (DSC).…”
Section: Resultsmentioning
confidence: 99%